Economic Valuation of Ecosystem Services of Mardhar Wetland of Rautahat, Nepal - Kanchan Timalsina; Shankar Tripathi; Sanjay Kumar Upadhaya (Journal of Wetlands Environmental Management, 2021)
Wetlands are ecologically diverse habitats that are integral to a range of ecosystem processes and provide many important ecosystem services. Despite of its vital role in the natural life support system, many wetlands are being misused and degraded due. Therefore, for the wise & sustainable use of wetlands, it is the utmost need to value the wetland. Taking this into consideration, the study estimated the total economic value of the Mardhar Wetland. The study identifies and prioritizes the major services of the wetland. The study used the market and nonmarket based valuation techniques to estimate the total economic value of the reservoir. Household surveys, focus group discussions, and interaction with visitors, fishermen plus wetland-based enterprises as well as district stakeholders were carried out to collect information. A purposive sampling method was carried out to select actors for the interview. Collected data from the field were analyzed quantitatively and quantitatively. The study identified thirteen major ecosystem services from the wetland. The study prioritized the major ecosystem services of the reservoir which include fish harvesting, ecotourism, and medicinal plant collection. The study estimated the total annual economic value of the reservoir which is USD US$ 10978.40 out of which the economic benefit from provisioning services account about 98.6%.